FAKTOR YANG MEMPENGARUHI CONSERVATISM ACCOUNTING DI INDUSTRI BARANG KONSUMSI - Jessica Halim; Susanto Salim (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The research aim to determine the effect of Leverage, Capital Intensity, Growth Opportunities, Firm Size, and Board of Commissioners on Conservatism Accounting in manufacturing company consumer goods industry listed on the Indonesia Stock Exchange in 2017-2019. This research uses a purposive sampling technique. There are 28 companies that have passed the criteria. Data processing techniques using multiple regression analysis by using IBM SPSS Statistics 22 and Microsoft Excel 2016 . The result in this research indicate that Leverage, Growth Opportunities, and Board of Commissioners has not significant negative effect on Conservatism Accounting, while Firm Size has positive and not significant effect on Conservatism Accounting. Only Capital Intensity have a significant positive effect on Conservatism Accounting.